Microbiomes of Caribbean Octocorals Vary Over Time but Are Resistant to Environmental Change - McCauley, Mark; Jackson, Colin R.; Goulet, Tamar L. (Frontiers in Microbiology, 2020)
The bacterial microbiome is an essential component of many corals, although knowledge of the microbiomes in scleractinian corals far exceeds that for octocorals. This study characterized the bacterial communities present in shallow water Caribbean gorgonian octocorals over time and space, in addition to determining the bacterial assemblages in gorgonians exposed to environmental perturbations. We found that seven shallow water Caribbean gorgonian species maintained distinct microbiomes and predominantly harbored two bacterial genera, Mycoplasma and Endozoicomonas. Representatives of these taxa accounted for over 70% of the sequences recovered, made up the three most common operational taxonomic units (OTUs), and were present in most of the gorgonian species. Host stable isotopic signatures, in addition to biochemical and algal (Symbiodiniaceae) parameters significantly correlated to the microbiome assemblages. Gorgonian species sampled in different seasons and/or in different years, exhibited significant shifts in the abundances of these bacterial OTUs, though there were few changes to overall bacterial diversity, or to the specific OTUs present. These shifts had minimal impact on the relative abundance of inferred functional proteins within the gorgonian corals. Sequences identified as Escherichia were ubiquitous in gorgonian colonies sampled from a lagoon but not in colonies sampled from a back reef. Exposure to increased temperature, and/or ultraviolet radiation or nutrient enrichment, led to few significant changes in the gorgonian coral microbiomes. While there were some shifts in the abundance of the prevalent bacteria, more commonly observed was ‘microbial switching’ between different OTUs identified within the same bacterial genus. The relative stability of gorgonian coral bacterial microbiome may potentially explain some of the resistance and resilience of Caribbean gorgonian corals against changing environmental conditions.